Exploring relation fraud, murder,and the Fraud Triangle - James W. Marquart; R. Alan Thompson (Journal of Economic Criminology, 2024)
This article examines the dynamics of relation fraud resulting in the murder of a grandparent by her grandson. While such instances are admittedly rare as forms of both murder and fraud more generally, this unique case nonetheless demonstrates that relation fraud resulting in murder is a significant problem worthy of further systematic empirical examination. In particular, Cressey’s Fraud Triangle is applied through a process of inductive analytic reasoning to explain the motivations of a grandson who defrauded and then killed his grandmother for her estate money in order to pay off escort debts and make plans for a new financial start post-murder. The paper contributes to the use of fraud typologies, relation fraud, the Fraud Triangle, elder crime victimology, and the use of analytic induction in theory development and refinement.